Imagens poéticas e representações da morte na lírica de Emily Dickinson e de Helena Kolody: convergências e contrastes - Ramos, Patricia de Lara (2014)
This study was carried out with the goal of juxtaposing poems of two poets who lived in different centuries and countries , but they had one thing in common: the writing on the theme of death, and from such juxtaposition emerged an analysis of the poetic images which converge and contrast with regard to the theme, thus demonstrating the importance of the imaginary in the interpretation of each image and understanding it as a creative act, able to assign different meanings to the images that should not be seen as something done/ready, as something that is transmitted hereditarily, but as something that holds several meanings which are grasped according to the feelings and emotions of each culture over time. To do so, poems of the North American poet Emily Dickinson and the contemporary Paranaense poet Helena Kolody were chosen. This work is centered on two categories of interpretation: Death, the unavoidable condition of all beings, which is addressed in this research based on some concepts brought by Biology, by Symbology, by Philosophy and by Christianity and then it presents the evolution of human towards death in the Western Christian society focusing solely on the studies of Ariès (2003), who starts his reflections by analyzing the medieval man and his relation to the death "tamed" death, in other words, familiar, close and moves his analysis to modern age, a period when society begins to express disgust toward death "forbidden", damned, rejected death. The second line of interpretation of this dissertation is related to the Imaginary, based on the thoughts of Gilbert Durand (1997), who regards human beings as a diverse set of symbolic forms, which permeate the entire collective imaginary in its most elementary form, but they also reconstruct and reinterpret themselves in a web of isomorphic images that interrelate in different ways in each culture